2019
DOI: 10.1007/s00167-019-05722-w
|View full text |Cite|
|
Sign up to set email alerts
|

Acute ACL reconstruction shows superior clinical results and can be performed safely without an increased risk of developing arthrofibrosis

Abstract: Purpose To compare acute ACL reconstruction (ACLR) within 8 days of injury with delayed reconstruction after normalized range of motion (ROM), 6-10 weeks after injury. It was hypothesized that acute ACL reconstruction with modern techniques is safe and can be beneficial in terms of patient-reported outcomes and range of motion. Methods The effect of acute and delayed ACLR was randomized studied on 70 patients with high recreational activity level, Tegner level 6 or more, between 2006 and 2013. Patient-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 38 publications
4
58
0
Order By: Relevance
“…As a result, subsequent studies adopted a similar accelerated rehabilitation protocol (12,13,28). This, along with the use of modern surgery technique, may explain why recent studies reported no clinical difference between early versus chronic ACLR supporting our findings (6,7,29 (31). Different studies reported other advantages of early surgery such as less muscle atrophy and less risk of exposing the knee to subsequent injuries associated with recurring instability such as meniscal and chondral injuries (11,32).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As a result, subsequent studies adopted a similar accelerated rehabilitation protocol (12,13,28). This, along with the use of modern surgery technique, may explain why recent studies reported no clinical difference between early versus chronic ACLR supporting our findings (6,7,29 (31). Different studies reported other advantages of early surgery such as less muscle atrophy and less risk of exposing the knee to subsequent injuries associated with recurring instability such as meniscal and chondral injuries (11,32).…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies, otherwise, reported no risk of arthrofibrosis with acute reconstruction showing similar or better outcomes than delayed ACLR (6,7). Furthermore, early surgery seems to be more cost-effective and can decrease the risk of subsequent meniscal or cartilage lesions by reducing the time between injury and reconstruction (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study found a significantly higher incidence of the lesion in women and a significantly smaller notch in those with cyclops lesions. 9 von Essen et al 39 found no difference in the incidence of the lesion in patients undergoing ACLR within 8 days versus 6 weeks after injury.…”
Section: Etiological Factorsmentioning
confidence: 97%
“…42,43 Interestingly, patients who had early ACLR were found to have significantly greater patellofemoral cartilage loss measured on magnetic resonance imaging at 5 years. 44 Eriksson et al 45 also compared early versus delayed and reported their outcomes at 6 months, 1 year, 46 and 2 years 47 and reported no significant differences except for more sick days leave taken by patients in the delayed group. The remining 3 RCTs also reported no significant differences (Table 4).…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…The remining 3 RCTs also reported no significant differences (Table 4). [41][42][43][44][45][46][47][48][49][50][51]…”
Section: Timing Of Surgerymentioning
confidence: 99%